Genome-Wide Association Studies Provide Insight Into the Genetic Determination for Hyperpigmentation of the Visceral Peritoneum in Broilers - Zhou, Guangyuan; Liu, Tianfei; Wang, Yan; Qu, Hao; Shu, Dingming; Jia, Xinzheng; Luo, Chenglong (Frontiers in Genetics, 2022)
Hyperpigmentation of the visceral peritoneum (HVP) has been becoming one of the most challenging problems in Yellow-feathered chicken production, which seriously affected chicken carcass quality traits. Detecting which genes dominantly impact pigmentation in the peritoneum tissues is of great benefit to the genetic improvement of HVP. To investigate the genetic mechanism of HVP in Yellow-feathered broilers, the genome-wide association studies (GWAS) were conducted in the F2 generation of a cross broiler population with 395 birds. Total 115,706 single nucleotide poly-morphisms (SNPs) of 122,415 were retained to identify quantitative trait loci (QTL) associated to HVP in chicken. The GWAS results based on the logistic mixed model (LMM) revealed that a narrow ge-nomic location on chromosomes 1 (49.2Mb-51.3Mb) was significantly associated (P ≤ 4.32× 10−7) with HVP, which contained 23 SNP makers related to 14 functional genes (MFNG, POLDIP3, POLR2F, PICK1, PDXP, SGSM3, RANGAP1, MYH9, RPL3, GALP3, LGALS1, MICALL1, ATF4 and CYP2D6). Four highly associated (P < 10-5) haplotype blocks of 0.80 kb (two SNPs), 0.06 kb (two SNPs), 0.95 kb (two SNPs) and 0.03kb (two SNPs) were identified with two, two, four and four distinct haplotypes. As a melanoma-associated gene, CYP2D6 were also possible involved in the development of HVP occurring in chicken with two significant variations (rs314284996 and rs317955795) in the promoter regions. Further tests revealed the expression of CYP2D6 was obviously higher in the visceral peritoneum tissue of chicken with HVP than that in the normal group (P<0.05). Our results provide a novel clue to understand the genetic mechanism of HVP generation in chicken, and the mapped QTL or candidate genes might serve for genomic selection to improve carcass quality in the Yellow-feathered chicken industry.